2012
DOI: 10.1101/gad.191056.112
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of α-KG-dependent histone and DNA demethylases by fumarate and succinate that are accumulated in mutations of FH and SDH tumor suppressors

Abstract: Two Krebs cycle genes, fumarate hydratase (FH) and succinate dehydrogenase (SDH), are mutated in a subset of human cancers, leading to accumulation of their substrates, fumarate and succinate, respectively. Here we demonstrate that fumarate and succinate are competitive inhibitors of multiple a-ketoglutarate (a-KG)-dependent dioxygenases, including histone demethylases, prolyl hydroxylases, collagen prolyl-4-hydroxylases, and the TET (ten-eleven translocation) family of 5-methlycytosine (5mC) hydroxylases. Kno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

21
850
1
6

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 915 publications
(878 citation statements)
references
References 50 publications
21
850
1
6
Order By: Relevance
“…Recent in vitro work has demonstrated that the accumulation of succinate in SDH-deficient tumors may lead to the inhibition of a-ketoglutarate-dependent enzymes, including TET family proteins, which convert 5-methylcytosine to 5-hmC. 26 In the current study, we examined 5-hmC levels by immunohistochemistry in a cohort of 30 genotyped GISTs and demonstrate that 5-hmC staining is absent in 90% of SDH-deficient GISTs, whereas loss of 5-hmC staining is seen in approximately 20% of KIT-or PDGFRA-mutant GISTs. The alteration of 5-hmC content through inhibition of TET activity seen in the SDH-deficient GISTs demonstrates the dysregulation of epigenetic modifications in these tumors.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Recent in vitro work has demonstrated that the accumulation of succinate in SDH-deficient tumors may lead to the inhibition of a-ketoglutarate-dependent enzymes, including TET family proteins, which convert 5-methylcytosine to 5-hmC. 26 In the current study, we examined 5-hmC levels by immunohistochemistry in a cohort of 30 genotyped GISTs and demonstrate that 5-hmC staining is absent in 90% of SDH-deficient GISTs, whereas loss of 5-hmC staining is seen in approximately 20% of KIT-or PDGFRA-mutant GISTs. The alteration of 5-hmC content through inhibition of TET activity seen in the SDH-deficient GISTs demonstrates the dysregulation of epigenetic modifications in these tumors.…”
Section: Discussionmentioning
confidence: 99%
“…24,25 Because of structural similarities between succinate and a-ketoglutarate, succinate is thought to inhibit the activity of a-ketoglutarate-dependent dioxygenase enzymes. 26 In particular, recent work has demonstrated that the TET family of DNA hydroxylases may be inhibited by elevated levels of succinate. 26 TET proteins have been shown to have a role in the regulation of DNA methylation.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Deficiencies in FH lead to high steady‐state concentrations of fumarate in the cell and surrounding extracellular space. In parallel to succinate, fumarate has been shown to competitively inhibit αKG‐dependent dioxygenase enzymes, resulting in a pseudohypoxic transcriptome through HIFα stabilization76 and a hypermethylator phenotype 76, 77. However, contrary to initial thoughts, now there is evidence to suggest that stabilization of HIF is not the driver of tumorigenesis in FH‐deficient tumors, and that a different candidate transcription factor—the nuclear‐related factor 2 (NRF2) pathway—may instead be involved 78, 79…”
Section: Mutations Of Mitochondrial (And Associated) Metabolic Enzymementioning
confidence: 99%